2005
DOI: 10.1007/s11126-005-2982-5
|View full text |Cite
|
Sign up to set email alerts
|

Review of Benzodiazepine use in Children and Adolescents

Abstract: Clinically, benzodiazepines are used in adult populations much more frequently than in children and adolescents. There may be a number of reasons for this disparity including a dearth of well controlled clinical studies and the issue of dependence associated with long term use. However, over a ten year span there has been nearly a three fold increase in the use patterns for these agents in the child population. In open studies much of the literature has indicated potentially useful results, but these findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
1
33
0
3
Order By: Relevance
“…108 Benzodiazepines Benzodiazepines (BDZs, Table 9) can be used to treat the short-term effects and somatic symptoms before a stage performance but because of their side effects, BDZs are not the medications of choice for sportrelated anxiety. 115,116 Their use is limited to short-term treatment in patients with severe anxiety symptoms for rapid effects before the effects of psychotherapy or SSRIs can be achieved. BZDs are often used for procedure-related anxiety.…”
Section: Selective Serotonin Re-uptake Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…108 Benzodiazepines Benzodiazepines (BDZs, Table 9) can be used to treat the short-term effects and somatic symptoms before a stage performance but because of their side effects, BDZs are not the medications of choice for sportrelated anxiety. 115,116 Their use is limited to short-term treatment in patients with severe anxiety symptoms for rapid effects before the effects of psychotherapy or SSRIs can be achieved. BZDs are often used for procedure-related anxiety.…”
Section: Selective Serotonin Re-uptake Inhibitorsmentioning
confidence: 99%
“…BZDs are often used for procedure-related anxiety. 108,115 BDZs bind to the benzodiazepine receptors in the central nervous system at the gamma aminobutyric acid-A (GABA-A) ligand-gated chloride channel complex and enhance the inhibitory effects of GABA. BDZs facilitate the chloride conductance through GABA-regulated channels.…”
Section: Selective Serotonin Re-uptake Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepines also do not carry the significant long-term side effects associated with antipsychotics including weight gain, dystonia, extrapyramidal symptoms and metabolic syndrome. Although several anecdotal and open-label studies have demonstrated benzodiazepines to be useful in treating obsessive-compulsive disorder (Bodkin & White, 1989;Tesar & Jenike, 1984) or anxiety disorders in children and adolescents (Biederman, 1990;Simeon & Ferguson, 1987), these findings have not been consistently replicated when more structured studies have been performed (Witek, Rojas, Alonso, Minami & Silva, 2005). Two double-blind, placebo-controlled studies failed to show that clonazepam was beneficial in treating symptoms of OCD either as monotherapy (Hollander et al, 2003) or in conjunction with sertraline (Crockett, Churchill & Davidson, 2004).…”
Section: Risperidonementioning
confidence: 99%
“…Prescriptions for benzodiazepines to youth increased 2.8-fold between 1987 and 1996 to an average of 5 per 1000 (Zito et al, 2003). A review of the literature on prescriptions for benzodiazepines in the treatment of psychiatric disorders among children and adolescents finds an increase in prescription rates despite a lack of rigorously designed studies assessing this treatment in non-adult populations (Witek et al, 2005).…”
Section: Medical Use Of Scheduled Medicationsmentioning
confidence: 99%